COMMUNITY CAPITALS POTENTIAL TO RESOLVE THE ISSUES FOR DEVELOPMENT OF UNDEVELOPED VILLAGES IN SOENG SANG DISTRICT, NAKHON RATCHASIMA PROVINCE: ศักยภาพทุนชุมชนในการแก้ไขปัญหาเพื่อพัฒนาหมู่บ้านล้าหลัง อำเภอเสิงสาง จังหวัดนครราชสีมา - วงษ์กาฬสินธุ์, สกุล (Research Community and Social Development Journal, 2018)
This research aims to 1) study context analysis, 2) analyze the problems and obstacles in implementing community of the development of the undeveloped villages, and 3) strengthen the community capacity building strategy plan in upgrading the development of the undeveloped village. Mixed methods that qualitative research with deep interviews and organizing a forum for community capital building strategies to enhance the development were used, and quantitative research was presented. The survey was conducted by questionnaire, including household representatives, community leaders, and committee members, in total of 7 villages, 330 participants in Serng Sang District, Nakhon Ratchasima, and using statistical data analysis. The research results revealed that the overall level was at a moderate level ( = 2.12) and the economic and financial sections were at a high level ( = 2.12). The overall problem and obstacle in bringing the community capital section in solving problem was in the medium level ( = 2.04) with the highest score in management level ( = 2.17) and the lowest score on community participation was found at a moderate level ( = 1.74). Thus, the criteria exposed 1) the foundation, 2) economic condition health, 3) sanitation knowledge, 4) education participation, 5) strength of the community, 6) natural Resources and environment, and 7) disaster and community risk.